ACTIVITY ANALYSIS OF STUDENT LEARNING AND SCIENTIFIC ATTITUDE IN BIOLOGY LEARNING USING LEARNING STRATEGIES GROUP TO GROUP EXCHANGE (GGE) IN CLASS XI SMAN 1 IA KUANTAN HILIR LESSONS YEAR 2010/2011 - Nursal '; Rosmaini S; Gusti Mulia (Program Studi Pendidikan Biologi, 2011)
Descriptive research has been conducted to determine the activity of learning and scientific attitude of students in learning Biology class XI IA in SMAN I Kuantan Hilir School Year 2010/2011 through the application of learning strategies GGE. The research was conducted in January 2011. The sample in the study were students in grade XI IA as many as 41 people consisting of 31 students are female and 10 male students. Parameters of learning activities and research is the scientific attitude of students in the learning process. Results showed an average activity of student learning as very good. The average score of the activity obtained at a meeting I amounting to 60.36% (poor category), II meeting at 71.54% (category enough). While the average attendance of 80.08% III (both categories), and IV meeting at 85.46% (very good category). The average scientific attitude of students at a meeting I of 55.28% (korigori less good), at the second meeting at 70.96% (both categories), the third meeting of 77.23% (both categories), and at the IV meeting at 87.33% (category very good). From the results of this study can be concluded that students assess GGE very good learning strategies to be applied to learning Biology because it can increase the activity of learning and scientific attitude of students.Keywords: Learning Activities, GGE Strategy, Student Scientific Attitude